On the hypothesized outflow control of tropical cyclone intensification. (9th April 2019) - Montgomery, Michael T.; Persing, John; Smith, Roger K.
Abstract : We present idealized, three‐dimensional, convection‐permitting numerical experiments to evaluate the premise of the revised theory of tropical cyclone intensification proposed by Emanuel, . The premise is that small‐scale turbulence in the upper tropospheric outflow layer determines the thermal stratification of the outflow and, in turn, an amplification of the system‐scale tangential wind field above the boundary layer. The aim of our article is to test whether parametrized small‐scale turbulence in the outflow region of a developing storm is an essential process in the spin‐up of the maximum tangential winds. Compared with the control experiment, in which the small‐scale, shear‐stratified turbulence is parametrized in the usual way based on a Richardson number criterion, the vortex in a calculation without a parametrized representation of vertical mixing above the boundary layer has similar evolution of intensity. Richardson number near‐criticality is found mainly in the upper‐level outflow. However, the present solutions indicate that eddy processes in the eyewall play a significant role in determining the structure of moist entropy surfaces in the upper‐level outflow. In the three‐dimensional model, these eddy processes are largely realizations of asymmetric deep convection and are not obviously governed by any Richardson‐number‐based criterion. The experiments do not support the premise on which the new theory is based. The results would appear to have ramifications for recent studies that invoke the new theory. Abstract : There is a hypothesis in the literature that subgrid‐scale mixing in the upper‐level outflow layer is the principal control on tropical cyclone intensification. An experiment (EX2) is performed where subgrid‐scale mixing in the vertical direction is suppressed above the boundary layer, compared to a control experiment (EX1) with complete physics. The results, as highlighted by the figure, show no significant difference in the simulated intensification between the two experiments. The study suggests that eddy processes in the eyewall play a significant role in determining the structure of moist entropy surfaces in the upper‐level outflow, as opposed to sub grid scale mixing there.